Trust Mediates Channel Integration And Viral Marketing In Repurchase Intention Golds Saving Products In PT Pegadaian Pringgan Medan (International Journal of Scientific Research and Management (IJSRM), 2023)
Omnichannel is a business model that integrates all sales channels the company owns into one overall system. Viral Marketing is a measure of how much clients can absorb and receive product-related information from social media. Customer trust is a mediating variable to increase customer repurchase intention in using the Pegadaian product. The purposes of this study are: (1) To find out and analyze the direct effect of integration channels (omnichannel), viral marketing, and trust on repurchase intention, (2) To find out and analyze the indirect effects of integration channels (omnichannel) and viral marketing on repurchase intention through customer trust. The number of samples in the study was 170 respondents. The sampling technique was carried out using nonprobability and purposive sampling methods. Data analysis used the Structural Equation Modeling (SEM) analysis method with model and structure measurements through Smart-PLS 3.0. The results of this study indicate that (1) omnichannel and viral marketing has a positive and significant effect on trust and repurchase intention. (2) Trust is able to mediate omnichannel and viral marketing channels on repurchase intention customers of Pegadaian Cab Pringgan Medan